Case Report: Dexmedetomidine for Intractable Clusters of Myoclonic Jerks and Paroxysmal Sympathetic Hyperactivity in Progressive Encephalomyelitis With Rigidity and Myoclonus - Fujino, Yuzo; Shiga, Kensuke; Hori, Masatoshi; Tamura, Aiko; Iizuka, Takahiro (Frontiers in Neurology, 2021)
Introduction: Progressive encephalomyelitis with rigidity and myoclonus (PERM) is a severe form of stiff-person spectrum disorder characterized by painful spasms, myoclonic jerks, hyperekplexia, brainstem dysfunction, and dysautonomia, which is sometimes resistant to γ-amino-butyric acid (GABA)-ergic agents. The response to immunotherapy varies depending on identified autoantibodies. We report a dramatic response to dexmedetomidine in a patient with glycine receptor (GlyR) antibody-positive PERM who developed intractable clusters of myoclonic jerks and paroxysmal sympathetic hyperactivity (PSH) that was highly refractory to conventional symptomatic treatment with GABAergic drugs and immunotherapy. Case Presentation: A 62-year-old Japanese man was transferred to our center for intermittent painful spasms that progressed in severity over the preceding 7 weeks. On admission, he had gaze-evoked nystagmus, and paroxysmal painful spasms/myoclonic jerks triggered by sound or touch. The myoclonic jerks rapidly worsened, along with the development of hyperekplexia, opisthotonus, and PSH, leading to prolonged apnea requiring mechanical ventilation. Brain and spinal cord magnetic resonance imaging was unremarkable. Cerebrospinal fluid (CSF) examination revealed mild pleocytosis and oligoclonal bands. Surface electromyography confirmed simultaneous agonist-antagonist continuous motor unit activity. Based on the clinico-electrophysiological features, PERM was suspected. He was initially treated with intravenous steroids, immunoglobulin, benzodiazepines, and propofol, but the symptoms persisted. On day 9, he received a continuous infusion of dexmedetomidine, which resulted in dramatic reduction in the frequency of clusters of myoclonic jerks and PSH. The effect of dexmedetomidine was confirmed by surface electromyography. The addition of plasma exchange resulted in further clinical improvement. GlyR antibodies were identified in the CSF but not the serum, leading to the diagnosis of GlyR antibody-positive PERM. Conclusions: PERM is an immune-mediated disorder, but dexmedetomidine, a highly selective α2-adrenergic agonist, may alleviate paroxysmal symptoms by decreasing noradrenergic neuronal activity, resulting in attenuation of antibody-mediated disinhibited increased motor and sympathetic activity. Dexmedetomidine may be useful as an adjunctive symptomatic therapy in PERM and related disorders.